Regional aspects of socio-economic modernization of the Republic of Кazakhstan. - Ashirbekova, L. Zh.; Tazhiyeva, S. K. (Journal of Economic Research & Business Administration, 2015)
In article it is considered social and economic modernizations of Kazakhstan during the post-crisis period which value considerably increased with transition consideration from export and raw economy on an innovative way of development. The author specifies that the regional policy of present Kazakhstan has to be directed on concentration of economic activity in the developed regional centers providing realization of economic and social modernization and therefore all long-term strategy and country development plans directed on modernization have to be based on the available capacity of regions of the country.